The Views of Al-Hidayah Mosque Congregation on the Presence of Children in the Mosque from the Perspective of Maṣlaḥah Mursalah - A'yun, Qurrota; Junaidy, Abdul Basith (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
Abstract: The presence of children in mosques is often a matter of debate in society. Its presence is considered to interfere with the solemnity of the congregation's worship, but on the other hand, prohibiting it can actually distance children from religious values. This article aims to analyze the presence of children in the mosque “al-Hidayah” in Geluran, Mloko, Sidoarjo, in relation to the theory of maṣlaḥah mursalah. This research employs a qualitative case study approach. Data collection was conducted through observation at the Al-Hidayah mosque and interviews with worshippers, mosque administrators, and children. The study's results showed that children's presence at the al-Hidayah Mosque was due to invitations from friends, parental orders, or the availability of activities in the mosque. This presence disturbs some pilgrims, while leaving others undisturbed. The presence of children in mosques aligns with the theory of maṣlaḥah mursalah, which defends the values of religion (hifdz al-dīn), education (hifdz al-aql), and the Islamic generation (hifdz al-nasl). In this case, the application of the principle of maṣlaḥah mursalah in the presence of children in the mosque is permissible on the condition that there is a good arrangement and guidance. Keywords: Maṣlaḥah Mursalah, children, mosque, worship. Abstrak: Kehadiran anak-anak di masjid sering menjadi perdebatan dalam masyarakat. Kehadirannya dianggap menganggu kekhusyu’an ibadah jama’ah namun dalam sisi lain, melarangnya justru dapat menjauhkan anak-anak dari nilai-nilai keagamaan. Artikel ini bertujuan untuk menganalisis kehadiran anak-anak di masjid al-Hidayah Geluran Mloko Sidoarjo untuk dianalisis dengan teori maṣlaḥah mursalah. Penelitian ini adalah penelitian kualitatif dengan pendekatan studi kasus. Pengumpulan data dilakukan melalui observasi di masjid al Hidayah dan wawancara terhadap jama'ah, pengurus masjid, dan anak-anak. Hasil penelitian menunjukkan bahwa kehadiran anak-anak di Masjid al-Hidayah karena ajakan teman, perintah orang tua, atau karena ada kegiatan di masjid. Kehadiran tersebut membuat jamaah ada yang terganggu dan ada yang tidak terganggu. Kehadiran anak-anak di masjid sejalan dengan teori maṣlaḥah mursalah dengan mempertahankan nilai agama (hifdz al-dīn), pendidikan (hifdz al-aql) dan generasi Islami (hifdz al-nasl). Maka dalam hal ini, penerapan prinsip maṣlaḥah mursalah dalam hadirnya anak-anak di masjid adalah diperbolehkan dengan syarat adanya pengaturan dan bimbingan yang baik. Kata Kunci: Maṣlaḥah Mursalah, anak-anak, masjid, ibadah